Unexpected benefit of haemoglobinopathy screening. (16th November 2010) - Topping, J; Adishesh, M
Abstract : Implementation of Universal antenatal screening policy of Haemoglobinopathy screening in Liverpool Women's Hospital resulted in incidental detection of higher levels of glycosylated haemoglobin in non-diabetic women. The authors designed a retrospective audit to find out whether these reports were of any significance. Data were collected over 1 year from the computerised booking and delivery notes. Women who were known diabetics were excluded. Information about previous medical history, previous pregnancy, current pregnancy, whether gestational diabetes developed, investigations and type of delivery were collected. Data were analysed using Microsoft excel. 118 women were indicated to have raised HbA1C in their Haemoglobinopathy screening. Out of these five were not found on the system. 27 women were excluded as they were diabetics. Out of remaining 86 non-diabetic women, majority were White British (73.3%). Among obstetric complications, 17.4% of women developed gestational diabetes. In the group who developed gestational diabetes, almost half were primigravidae, 73.3% had family history of diabetes and 60% had body mass index (BMI) <30. The authors concluded that it is important not to ignore the raised HbA1C in Haemoglobinopathy screening as this helps to identify women who develop gestational diabetes. Family history is a risk factor. Surprisingly, BMI has not influenced incidence of diabetes in these women. The authors recommend that a comprehensive study will help to find the implications of these results. A standardised management plan must be devised in management of such women but cost effectiveness of the additional investigations must be considered.